Vacuum Frying of Desalted Grass Carp (Ctenopharyngodon idellus) Fillets - Chen, H.; Zhang, M.; Fang, Zhongxiang (Taylor & Francis, 2014)
The objective of this study was to investigate the effects of vacuum frying on the product quality of desalted grass carp fillets. Parameters of included moisture content, oil content, color values, and textures (hardness, chewiness, and springiness) were used to evaluate the pro- duct quality. Results showed that with increasing vacuum frying temperature and time, the moisture content of fillets decreased while the oil content increased, and hardness increased quickly. The hardness and chewiness values of vacuum-fried samples were both higher than those of atmospheric fried samples. However, there was no significant change in L* among four different temperature/ vacuum-frying combinations. The results also indicated that vacuum frying at 0.08 MPa and 100°C–110°C for 15 min can produce crisp grass carp fillets with lower moisture and oil contents as well as good color and texture quality.